Xanthohumol inhibits tau protein aggregation and protects cells against tau aggregates. Issue 12 (3rd December 2019) - Zhang, Mohan; Wu, Qiuping; Yao, Xuanbao; Zhao, Junyi; Zhong, Weicong; Liu, Qiong; Xiao, Shifeng
Abstract : Xanthohumol is shown to interact with tau protein and inhibit its aggregation. Abstract : Alzheimer's disease (AD) is a neurodegenerative disease. The molecular mechanisms of AD are not yet clear, and no effective treatments are available to cure AD. Because of the huge number of patients and related costs, it is urgent to discover new medicines to prevent or cure AD. In this study, xanthohumol (XN), a natural botanic compound, is found to inhibit tau protein aggregation and disaggregate tau fibrils. XN directly interacts with tau protein at sites sporadically located in all four repeating domains with a K d value of 52 μM. Binding with XN does not alter the secondary structures of tau protein. Cellular experiments showed that XN exhibits little cytotoxicity and attenuates apoptosis induced by tau oligomers. The results provide preliminary experimental data to develop XN into medicines, food products, or nutritional supplements for AD. The findings also provide data for computational drug design.